Isolation and screening of an extracellular organic solvent-tolerant protease producer - Geok, Lee Poh; Nyonya, Che; Razak, Abdul; Abd Rahman, Raja Noor Zaliha (Elsevier Science B.V., 2003)
An extracellular organic solvent-tolerant protease producer has been successfully isolated out of 11 isolates of benzene-toluene-xylene-ethylbenzene (BTEX) tolerant bacteria. This organic solvent-tolerant microorganism was found to be a polycyclic-aromatic-hydrocarbons (PAHs) degrader and identified as Pseudomonas aeruginosa strain K. It was selected based on the stability of its proteolytic enzyme in the presence of various organic solvents. P. aeruginosa strain K protease tolerated up to at least 50% (v/v) of benzene, n-hexane, 1-decanol, isooctane and n-hexadecane and was also stable in the presence of 25% (v/v) n-decane and n-dodecane. This enzyme strain K was activated 2.5, 1.5 and 1.2 times by 75% (v/v) of 1-decanol, isooctane and n-dodecane, respectively. This organic solvent stable protease could be used as a biocatalyst for enzymatic synthesis in the presence of organic solvents.